2010
DOI: 10.1016/j.drudis.2010.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzymes and drug discovery in cardiovascular diseases

Abstract: Angiotensin-converting enzyme (ACE) is a major target in the treatment of cardiovascular diseases (CVDs). In addition to ACE, ACE2 -which is a homolog of ACE and promotes the degradation of angiotensin II (AngII) to Ang (1-7) -has been recognized recently as a potential therapeutic target in the management of CVDs. This article reviews different metabolic pathways of ACE and ACE2 (AngI-AngII-AT1 receptors and AngI-Ang (1-7)-Mas receptors) in the regulation of cardiovascular function and their potential in new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 102 publications
(206 reference statements)
1
47
0
1
Order By: Relevance
“…Mammalian ACE activity in the ChP4 was high and localized to the BBM (5,7,59). Although ACE2 and NEP mRNA were detected in the ChP, we are not aware of any studies measuring their relative activity (21,72). We found that ACE2 activity was 3.5-fold higher than ACE and 2.4-fold higher than NEP.…”
Section: Control Bmxmentioning
confidence: 59%
“…Mammalian ACE activity in the ChP4 was high and localized to the BBM (5,7,59). Although ACE2 and NEP mRNA were detected in the ChP, we are not aware of any studies measuring their relative activity (21,72). We found that ACE2 activity was 3.5-fold higher than ACE and 2.4-fold higher than NEP.…”
Section: Control Bmxmentioning
confidence: 59%
“…Studies by Crackower et al (7) using three different models of hypertension have shown an inverse relationship between ACE2 mRNA/protein levels and blood pressure. Additionally, since ACE and ACE2 are involved in generating and/or degrading the bioactive peptides of the RAS, levels of these peptidases predicted the occurrence of vasoconstriction over dilatation or the dominance of pathophysiological stimuli over beneficial conditions (6,37). Analysis of angiotensin fragments suggested that greater expression of ACE or a lower expression of ACE2 might have resulted in lowering of Ang (1-7) and increasing of ANG II in the HS-fed obese rats.…”
Section: Discussionmentioning
confidence: 94%
“…Activation of the AT2R provides many opposing effects such as vasodilation, hypotension, apoptosis, antihypertrophic and inhibition of the AT1R [110]. There is a great deal of complexity in the RAS pathway, including numerous factors and receptors that participate in the pathway such as ACE2, Ang(1–7) and Ang(1–12) [111,112]. However, the AT1R and AT2R are the major contributors in transduction of extracellular signals to elicit the effects of Ang II.…”
Section: Interaction Between Mirnas and The Ras Related To Ir Injurymentioning
confidence: 99%